2018
DOI: 10.1083/jcb.201802077
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin B2 can compensate for Cyclin B1 in oocyte meiosis I

Abstract: Mammalian oocytes are arrested at the prophase of the first meiotic division for months and even years, depending on species. Meiotic resumption of fully grown oocytes requires activation of M-phase-promoting factor (MPF), which is composed of Cyclin B1 and cyclin-dependent kinase 1 (CDK1). It has long been believed that Cyclin B1 synthesis/accumulation and its interaction with CDK1 is a prerequisite for MPF activation in oocytes. In this study, we revealed that oocyte meiotic resumption occurred in the absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 49 publications
7
46
2
Order By: Relevance
“…In experiments investigating the function of the spindle component NDC80/HEC1 during meiotic prophase, knockdown of CCNB2 with morpholino oligonucleotides (MO) markedly decreased mouse oocyte meiotic re-entry (Gui and Homer, 2013). Similar findings were reported in a recent study investigating CCNB1 function in oocytes (Li et al, 2018). Recent data also demonstrated that the rates of translation of the two major CCNBs, B1 and B2, are regulated in distinct fashions during meiotic prophase .…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…In experiments investigating the function of the spindle component NDC80/HEC1 during meiotic prophase, knockdown of CCNB2 with morpholino oligonucleotides (MO) markedly decreased mouse oocyte meiotic re-entry (Gui and Homer, 2013). Similar findings were reported in a recent study investigating CCNB1 function in oocytes (Li et al, 2018). Recent data also demonstrated that the rates of translation of the two major CCNBs, B1 and B2, are regulated in distinct fashions during meiotic prophase .…”
Section: Introductionsupporting
confidence: 71%
“…3A). Recently, it was reported that oocyte-specific knockout of CCNB1 results in the overexpression of CCNB2 (Li et al, 2018); however, CCNB1 expression was not affected in Ccnb2 −/− oocytes ( Fig. S2A,B).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Notwithstanding this observation, the upregulation of Cyclin B clearly plays a positive role in reinforcing CDK1/MPF activity and thus driving meiotic cycle progression. As such, our study correlates the resumption of meiosis with the synthesis of the regulatory subunit of MPF, namely cyclin B1/2, as supported by the fact that the level of MPF activity is known to depend on the amount of cyclin B present [ 22 , 39 , 40 ]. Thus, the fact that the MPF components in aged GV oocytes are apparently more expressed (but not necessarily fully active) and that they are then rapidly activated during their maturation (in AF versus YF oocytes) contributes to the observed acceleration of the AF oocytes meiotic progression.…”
Section: Discussionmentioning
confidence: 60%
“…Through oocyte-specific depletion, we demonstrate here that Snf2h (also known as Smarca5) plays an essential role in oocyte meiotic resumption in mouse. Loss of function of Snf2h results in dysregulation of a number of genes involved in MPF activation and oocyte maturation, including Ccnb2 (Li et al 2018), Prkaca (Bornslaeger et al 1986), Prkar2b (Yoon et al 2018), and Ndc80 (Gui and Homer 2013). In addition, ATAC-seq analysis revealed a global alteration in chromatin accessibility in Snf2hdeficient oocytes and a significant decrease of chromatin accessibility at the Prkar2b promoter.…”
mentioning
confidence: 99%